2016
DOI: 10.3758/s13414-016-1194-4
|View full text |Cite
|
Sign up to set email alerts
|

Framing faces: Frame alignment impacts holistic face perception

Abstract: Traditional accounts of face perception emphasise the importance of the prototypical configuration of features within faces. However, here we probe influences of more general perceptual grouping mechanisms on holistic face perception. Participants made part-matching judgments about composite faces presented in intact external oval frames or frames made from misaligned oval parts. This manipulation served to disrupt basic perceptual grouping cues that facilitate the grouping of the two face halves together. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…Indeed, the idea that some stimuli form perceptual wholes with properties over and above those of their constituent parts can of course be traced back to Gestalt psychology and beyond. Nonetheless, it is now accepted that perceptual organization can influence attentional selection, and that an object formed by perceptual organization can capture attention that may facilitate or interfere with task performance object-based attention and perceptual grouping (Curby & Entenman, 2016; Curby et al, 2013, 2016; Kimchi, 2009; Retter & Rossion, 2015). For example, Kimchi, Yeshurun, and Cohen-Savransky (2007) showed that a task-irrelevant diamond-like object (a contour object formed by four rotated “L” letters) evoked an object-based attention effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the idea that some stimuli form perceptual wholes with properties over and above those of their constituent parts can of course be traced back to Gestalt psychology and beyond. Nonetheless, it is now accepted that perceptual organization can influence attentional selection, and that an object formed by perceptual organization can capture attention that may facilitate or interfere with task performance object-based attention and perceptual grouping (Curby & Entenman, 2016; Curby et al, 2013, 2016; Kimchi, 2009; Retter & Rossion, 2015). For example, Kimchi, Yeshurun, and Cohen-Savransky (2007) showed that a task-irrelevant diamond-like object (a contour object formed by four rotated “L” letters) evoked an object-based attention effect.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the composite effect may reflect contributions from different sources of interference that range from the presence of a novel holistic perceptual representation of the composite in the aligned condition to problems in selectively attending and responding to information from the different parts of the aligned stimuli. Recent studies have shown the importance of such factors by linking the composite effect to other phenomena involving selective attention (Chua & Gauthier, 2016; Chua, Richler, & Gauthier, 2014, 2015; Fitousi, 2015, 2016) or object-based attention and perceptual grouping (Curby & Entenman, 2016; Curby, Entenman, & Fleming, 2016; Curby, Goldstein, & Blacker, 2013; Retter & Rossion, 2015). As Murphy et al (2016) point out, such findings imply that although the composite effect involves holistic perception of faces, it is not in itself a process-pure measure.…”
mentioning
confidence: 99%
“…Notably, a differential onset of the timing of holistic processing markers for faces and these stimuli rich in grouping cues would have been inconsistent with this account. Thus, the holistic processing of these two classes of stimuli not only show a similarly rapid onset, but previous work suggests that manipulating the perception (Curby et al, 2016 ) or presence (Curby et al, 2013 ; Curby & Entenman, 2016 ) of grouping cues, impacts holistic processing of faces. Further, consistent with a competition for overlapping mechanisms, concurrently processing face and these non-face stimuli rich in Gestalt cues produced symmetrical interference effects with holistic processing of both stimulus classes showing similar interference effects (Curby & Moerel, 2019 ).…”
Section: Discussionmentioning
confidence: 89%
“…Half of these pairs consisted of 12 female composite face pairs while the other half consisted of 12 male composite face pairs. Given that misalignment of inner face features can reduce the composite face effect (Curby & Entenman, 2016) (although see (Kurbel, Meinhardt-Injac, Persike, & Meinhardt, 2021) for robust results regardless of perceptual fit), we ensured as much as possible that each individual face was paired with a same-gender face of similar size/shape and skin tone. Also, as recommended for the composite face task (Rossion & Retter, 2015), we included a small gap between the top and bottom halves of each composite face.…”
Section: Methodsmentioning
confidence: 99%